From Vietnam, VA, to Iraq, CA: The Spectrality of Violence in An-My Lê’s Small Wars and 29 Palms - Barbara Kowalczuk (Sillages Critiques)
This paper focuses on two of the three photographic projects included in An-My Lê’s Small Wars (2005). The first one, Small Wars (1999–2002) represents Vietnam War reenactors staging combat in the Virginian forest. In the second project, 29 Palms (2003–2004), Lê turns her camera on United States Marines preparing for deployment in Iraq in the California desert. In the series, warfare is either reenacted or rehearsed without the violent outcome of combat being tangibly represented. However, the spectrality of past and impending violence permeates the photographs and confirms the haunting legacy of war iconography. We will examine how Lê uses the American landscape and creates images haunted by the invisible visibility of violence.